Unfractionated heparin may improve near-term survival in patients admitted to the ICU with sepsis attributed to pneumonia: an observational study using the MIMIC-IV database - Shusheng Fang; Yali Wang; Wenyu Nan; Yanhao Feng; Wen Su; Yiming Wang; Xiaodong Jiang (Frontiers in Pharmacology)
IntroductionLimited data are available on the use, duration, and dosage of anticoagulant therapy in patients with pneumonia-induced sepsis, and the survival benefits of heparin remain uncertain. This study aimed to assess whether heparin administration improves near-term survival in critically ill patients with pneumonia-induced sepsis and identify the optimal dosage and treatment duration.MethodsThis study utilized the Medical Information Mart for Intensive Care-IV (MIMIC-IV) database. The variance inflation factor was employed to exclude highly collinear variables. Propensity score matching (PSM), the Cox proportional hazards model, and Cox regression subgroup analysis were used to evaluate the outcomes of subcutaneous heparin prophylactic anticoagulation after intensive care unit (ICU) admission. The primary outcomes were 30-, 45-, and 60-d mortality rates. Secondary outcomes included ICU length of stay (LOS_ICU), hospital length of stay (LOS_Hospital), in-hospital mortality, and the incidence of gastrointestinal bleeding.ResultsWe enrolled 1,586 adult patients with pneumonia-induced sepsis. After PSM, 1,176 patients remained (588 in the heparin group and 588 in the non-heparin group). The 45-d survival rate was significantly higher in the heparin-treated group than that in the non-heparin group (84.4% vs. 79.4%; HR: 0.75; 95% CI: 0.572–0.83; adjusted HR: 0.73, 95% CI: 0.563–0.964; P < 0.05). LOS_ICU and LOS_Hospital were significantly shorter in the heparin group (P < 0.001), with no significant difference in gastrointestinal bleeding incidence between the two groups. Cox proportional hazards models demonstrated that heparin dose and duration were strongly associated with 45-d survival. Subgroup analysis indicated a significant survival advantage in patients aged 18–60 years, without diabetes, chronic obstructive pulmonary disease, or stage 1 acute kidney injury, who received a daily heparin dose of 3 mL for more than 7 d.ConclusionOur study found that early administration of heparin, particularly in sufficient doses (Heparin Sodium 5,000 units/mL, 1 mL per dose, three times daily (TID)) for more than 7 d, was associated with reduced near-term mortality in critically ill patients with pneumonia-induced sepsis. These findings underscore the potential benefits of anticoagulant therapy in this high-risk patient population.